Cloud Computing For Supply Chain Management - Ms.Harshala Bhoir; Mrs.Ranjana Patil Principal (International Journal of Innovations in Engineering Research and Technology, 2021)
Cloud computing can give the ability of flexibly outsourcing software for supply chain collaboration and infrastructure needs in a better way. Instead of maintaining and paying for maximum use this technology puts forward the method that provides flexibility to add on the way, depending upon the overall business process and network model of supply chain. Ahead of the usual technology publicity, the worth of cloud computing is that it can be a right technology for supporting and managing a constantly cha nging and dynamic network and thus for supply chain management. Because now a day these are the exact visibility and supply chain collaboration needs. Efficient supply chains are a vital necessity for many c ompanies. Supply chain management acts on operational processes, divergent and consolidated information flows and interaction processes with a variety of business partners.